Ovarian response to equine chorionic gonadotrophin. (eCG) and GnRH in buffalo heifers (Bubalus bubalis) - Singh, C; Madan, M L (The Indian Journal of Animal Sciences, 2012)
Murrah buffalo heifers (6) of 24 to 25 months of age were treated with PGF₂α and eCG combination to study the ovarian potential of prepubertal buffaloes for ovulation and endocrine secretion. GnRH (Fertagy) 200 mg was injected (I/V) in 3 heifers (experimental) while saline (2 ml) was injected (I/V) in remaining 3 heifers (control) at estrus. The total number of palpable follicles on ovaries were 5.67 ± 1 .67 and 5.00 ± 1.53 while plasma estrogen concentration was 189.70 ± 25.34 pg/ml and 199.62 ± 19.28 pg/ml, respectively, in experimental and control group at estrus. The ovulations were synchronized (within 14.67 ± 1.77 hr) after GnRH injection while it was delayed (within 61.60 ± 13.74 hr) in saline-treated heifers. The estrogen concentration also declined following synchronized ovulation within 24 hr. The synchronized ovulation followed earlier (day 7 of estrus) associated with higher (5.38 ± 1.44 ng/ml) release of plasma progesterone in experimental compared to control (2.81 ± 1.48 ng/ml, days). The peak estrogen concentration and number o follicles in experimental (r = 0.99) and control (r = 0.94) groups and the peak plasma progesterone concentration and number of corpus luteum in experimental (r = 0.49) and control (r = 0.99) groups were highly correlated.